Time to Relapse and Its Predictors among Children with Nephrotic Syndrome in Comprehensive Specialized Hospitals, Tigray, Ethiopia, 2019 - Miliete Gebrehiwot; Mekuria Kassa; Haftom Gebrehiwot; Migbar Sibhat (International Journal of Pediatrics)
Background. Relapse in children with nephrotic syndrome leads to a variety of complications due to prolonged treatment and potential dependency on steroids. However, there is no study conducted to determine the incidence and predictive factors of relapse for nephrotic syndrome in Ethiopia, especially in children. Thus, this study aimed to assess the incidence of relapse and its predictors among children with nephrotic syndrome in Ethiopia. Methods. A retrospective study was conducted by reviewing all charts of children with an initial diagnosis of the nephrotic syndrome in tertiary hospitals from 2011 to 2018. Charts of children with a diagnosis of steroid-resistant cases were excluded. The extraction tool was used for data collection, Epi-data manager V-4.4.2 for data entry, and Stata V-14 for cleaning and analysis. Kaplan-Meier curve, log-rank test, life table, and crude hazard ratios were used to describe the data and adjusted hazard ratios with 95% CI and P value for analysis. Median relapse time, incidence rate of relapse, and cumulative relapse probabilities at a certain time interval were computed. Bivariable and multivariate analyses were performed using the Cox proportional hazard regression to identify the factors associated with relapse. Any variable at P<0.25 in the bivariable analysis was transferred to multivariate analysis. Then, the adjusted hazard ratio with 95% CI and P≤0.05 was used to report the association and to test the statistical significance, respectively. Finally, texts, tables, and graphs were used to present the results. Results and Conclusion. Majority, 64.5% (40/66), of relapses were recorded in the first 12 months of follow-up. The incidence rate of relapse was 42.6 per 1000 child-month-observations with an overall 1454 child-month-observations and the median relapse time of 16 months. Having undernutrition [AHR=3.44; 95% CI 1.78-6.65], elevated triglyceride [AHR=3.37; 95% CI 1.04-10.90], decreased serum albumin level [AHR=3.51; 95% CI 1.81-6.80], and rural residence [AHR=4.00; 95% CI 1.49-10.76] increased the hazard of relapse. Conclusion and Recommendation. Relapse was higher in the first year of the follow-up period. Undernutrition, hypoalbuminemia, hypertriglyceridemia, and being from rural areas were independent predictors of relapse. A focused evaluation of those predictors during the initial diagnosis of the disease is compulsory.